Strategi Pendidikan Karakter dalam Menumbuhkan Percaya Diri Siswa Disabilitas di MAN 2 Sleman - Thoriq Majid Rahmadias; Muh Wasith Achadi (Jurnal Ragam Pengabdian, 2026)
Students with disabilities are a group that cannot be overlooked in the education and learning process. Often, due to their limitations and societal perceptions that underestimate their abilities, they tend to lack self-confidence, which in turn hinders them from maximizing their individual potential. This article discusses strategies implemented by MAN 2 Sleman to instill and foster self-confidence among students with disabilities. The study employed a qualitative method with a case study approach. Data were collected through interviews, observations, and documentation. The results revealed three key strategies. First, the school provides equal access to education for students with disabilities. In the learning context, teachers at MAN 2 Sleman are required to be creative in designing instruction so that teaching materials and methods are accessible to students with disabilities. Second, the school implements a compensatory program as a special enrichment initiative for students with disabilities, which includes consultation services to accommodate their complaints and aspirations, mapping of their interests and talents, and encouragement to participate in various extracurricular activities as outlets for their interests and talents. They are also involved in various competitions to build their self-confidence. Third, the school fosters an inclusive environment by cultivating an attitude of openness among non-disabled students and establishing a disability-friendly community.